Pretreatment of sweet sorghum silages with Lactobacillus plantarum and cellulase with two different raw material characteristics: fermentation profile, carbohydrate composition, in vitro rumen fermentation and microbiota communities - Zhiqiang Sun; Yuan Li; Shuangye Li; Siyuan Wang; Siyi Li; Yan Ke; Run Gao; Lei Wang; Zhenming Zhou; Zhe Wu; Zhu Yu (Chemical and Biological Technologies in Agriculture)
Abstract Background Sweet sorghum (Sorghum bicolor (L.) Moench) is a popular forage crop in arid and semi-arid areas due to its high drought tolerance, rapid growth, and low production costs. In addition, sweet sorghum, has relatively specific ensiling characteristics because of its high moisture content and sufficient amount of water soluble carbohydrates. Therefore, it is crucial to investigate the raw material characteristics and exogenous additive pretreatment for the regulation of silage quality. This study aimed to evaluate the effects of Lactobacillus plantarum (LP) and cellulase (CEL) on the fermentation profile, carbohydrate composition, in vitro rumen fermentation and microbiota communities of sweet sorghum silages with two different raw material characteristics (fresh sweet sorghum material (MC1); sweet sorghum material wilted outdoors for 6 h after chopping (MC2)). Results In this study, the sweet sorghum treatments were: control (without additives), LP, CEL, or a combination of LP and CEL (LP_CEL). All treated sweet sorghum samples were ensiled for 30 d. A higher content of lactic acid, propionic acid, D-fructose, glucose, sucrose and a lower content of structural carbohydrates were observed in MC1 silage than in MC2 silage. In MC2 silage, the addition of CEL or LP_CEL decreased the content of structural carbohydrates, while it increased the content of D-fructose, glucose, D-arabinose, xylitol, maltose and trehalose (P < 0.05). The in vitro gas production at 48 h was greater in MC1 silage than in MC2 silage, and the addition of CEL or LP_CEL increased the in vitro dry matter digestibility in MC2 silage (P < 0.05). After 30 d of ensiling, disaccharides such as sucrose, maltose and alginate were almost entirely utilized by the microorganisms, while more-consumed monosaccharides included D-fructose, glucose and L-rhamnose. Lactobacillus was the dominant genus (> 80% relative abundance) in all silage samples. Conclusions Raw material characteristics determine carbohydrate composition, in vitro digestibility, and microbial community of sweet sorghum silage. For wilted sweet sorghum with relatively low moisture content, pretreatment with CEL or LP_CEL reduced the structural carbohydrate content, increased the nonstructural carbohydrate content, and improved the digestibility of the silage. However, additives had no obvious impact on enhancing the fermentation quality of sweet sorghum silage for two raw material characteristics. Graphical abstract